222Rn in Some Underground Water-Samples and Examination of Correlation to 238U Concentration - W. KADI, MOHAMMAD (Asian Journal of Chemistry, 2024)
The concentration of 238U and 222Rn has been assessed in underground water samples collected from the Makkah Al-Mukarramah area west of Saudi Arabia. Observed radon activities lie in the range 0.6-3.9 Bq/L. This range is within the natural limits of concentration of radon. Radon concentrations observed in this study are compared to those observed in a study of radon concentrations in the central region of Saudi Arabia. In the experimental setup, CR-39 detectors are exposed to radon emanating from water samples for 30 d. Uranium concentrations lie within the range 1.02-31.97 μg/L. No direct correlation is found between concentrations of the two isotopes; however radon content in water is much higher than that of uranium.